Soft palate reconstruction after radionecrosis: Combined anterolateral thigh adipofascial and nasoseptal flaps. Issue 4 (August 2018) - Zenga, Joseph; Sharon, Jeffrey D.; Gross, Jennifer; Gantz, Jay; Pipkorn, Patrik
Abstract: Although radiation-based treatment for nasopharyngeal cancer may achieve excellent long term oncologic results, late effects of therapy may lead to soft tissue radionecrosis and velopharyngeal insufficiency (VPI). Repair of these oro- and nasopharyngeal defects presents a complex reconstructive challenge. We present a case of a long-term survivor treated with chemoradiotherapy for nasopharyngeal cancer who developed progressive dysphagia, velopharyngeal insufficiency, and radionecrosis of the nasopharynx and soft palate, leading to tracheostomy and gastrostomy tube dependence. A staged reconstruction was performed, initially with a tubed nasoseptal flap for a creation of a mucosal-lined nasopharyngeal port. An adipofascial anterolateral thigh free flap was subsequently performed for soft palate reconstruction. Within 2 months, the oropharyngeal reconstruction had remucosalized and she was decannulated, taking an oral diet. Her speech was intelligible and she had good nasal breathing without symptoms of velopharyngeal insufficiency.